Applying Linear Programming to the Design of Ultimate Pit Limits - Meyer, Manfred (Management Science, 1969)
The purpose of this paper is to demonstrate the use of a Linear Programming model in open pit mine evaluation. The primary conditions to be incorporated into the model are the course and the inclination of the ore vein, and, during the whole life of the mine, safe slope angles to be maintained. Subject to this the objective of running a mine is assumed to be maximizing the direct operating profits which consist of proceeds from the sale of ore minus direct operating cost of extraction, transportation, and upgrading. First the Linear Programming model is developed, and subsequently some computational aspects are treated.